Spectral Self-Compression of Partially Coherent Pulses - M. Sukiasyan
We numerically studied the nonlinear effect of spectral self-compression: the spectral analogue of temporal self-compression. The study is done for pulses with random modulations of amplitude and phase, and for pulses that have random modulations of both amplitude and phase.
Keywords: Physics; Electronics; radiowave and microwave technology; direct energy conversion and storage